Longitudinal Functional Brain Mapping in Supernormals. (23rd November 2017) - Wang, Xixi; Ren, Ping; Baran, Timothy M; Raizada, Rajeev D S; Mapstone, Mark; Lin, Feng; ,
Abstract: Prevention of age-related cognitive decline is an increasingly important topic. Recently, increased attention is being directed at understanding biological models of successful cognitive aging. Here, we examined resting-state brain regional low-frequency oscillations using functional magnetic resonance imaging in 19 older adults with excellent cognitive abilities (Supernormals), 28 older adults with normative cognition, 57 older adults with amnestic mild cognitive impairment, and 26 with Alzheimer's disease. We identified a "Supernormal map", a set of regions whose oscillations were resistant to the aging-associated neurodegenerative process, including the right fusiform gyrus, right middle frontal gyrus, right anterior cingulate cortex, left middle temporal gyrus, left precentral gyrus, and left orbitofrontal cortex. The map was unique to the Supernormals, differentiated this group from cognitive average-ager comparisons, and predicted a 1-year change in global cognition (indexed by the Montreal Cognitive Assessment scores, adjusted R 2 = 0.68). The map was also correlated to Alzheimer's pathophysiological features (beta-amyloid/pTau ratio, adjusted R 2 = 0.66) in participants with and without cognitive impairment. These findings in phenotypically successful cognitive agers suggest a divergent pattern of brain regions that may either reflect inherent neural integrity that contributes to Supernormals' cognitive success, or alternatively indicate adaptive reorganization to the demands of aging.